PENGARUH KNOWLEDGE MANAGEMENT DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (STUDI PADA PT. ADIRA MULTI FINANCE, TBK. CABANG MAKASSAR 4) - Ansar, Ansar (Indonesian Journal Of Economy Studies, 2023)
The aim of this research is to determine the partial and simultaneous effects of the variables of knowledge management and organizational culture on employee performance. In this study, the researcher employed a saturated sample, obtaining a total of 54 respondents. The research method used is an associative approach with a multiple regression model, aided by SPSS 25.The results of this study indicate that knowledge management has a significant positive influence on employee performance, and organizational culture also has a significant positive influence on employee performance. Simultaneously, both variables have a positive and significant impact on employee performance.